Developing and Validating a Holistic Islamic Religiosity Scale: Evidence from Indonesian Islamic Banking Consumers - Wenda Wahyu Christiyanto; Vanessa Gaffar (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Religiosity has been widely recognized as an important determinant of consumer attitudes and behavior. However, existing measures are often developed within non-Islamic contexts or focus on specific aspects of Muslim religiosity, resulting in limited consensus regarding a comprehensive measure grounded in Islamic teachings. In particular, there remains a lack of validated instruments that integrate the foundational Islamic concepts of iman (faith) and taqwa (piety) into a holistic construct suitable for contemporary Muslim consumer contexts. This study aims to develop and validate a new construct, namely Holistic Islamic Religiosity, among Islamic banking consumers in Indonesia. A mixed-method sequential exploratory design was employed, utilizing a Systematic Literature Review of 76 selected articles in the qualitative phase, followed by a quantitative survey of 403 customers analyzed via Exploratory Factor Analysis and Confirmatory Factor Analysis. The findings demonstrate that Holistic Islamic Religiosity comprises two interrelated dimensions: Faith (four indicators: belief in God, the importance of religion, its influence on life, and social responsibility) and Piety (three indicators: ritual worship, daily supplication, and avoidance of sinful behavior). The model exhibits satisfactory validity and reliability, contributing a theoretically grounded instrument for future research in Islamic banking, finance, marketing, and halal tourism.